2015
DOI: 10.1186/s40780-015-0031-6
|View full text |Cite
|
Sign up to set email alerts
|

PK/PD analysis of biapenem in patients undergoing continuous hemodiafiltration

Abstract: BackgroundContinuous hemodiafiltration (CHDF) is used as renal replacement therapy for critically ill patients with renal failure, and to treat hypercytokinemia. Since CHDF also clears therapeutic agents, drug pharmacokinetics (PK) should be dependent upon CHDF conditions. Although the antibiotic biapenem (BIPM) is used in patients undergoing CHDF, the optimal therapeutic regimen in such patients has not been fully clarified. In this study, we investigated the PK of BIPM in patients with various levels of rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
3
0
3
Order By: Relevance
“…Flucloxacillin Ultrafiltration rate: 57 ± 9 ml/min 4.0 g q8h (Meyer et al, 2003) --1 g q8h 1h infusion (Onichimowski et al, 2020b) Dialysate rate: 20-35 ml/kg/h 2 g q12 h; or Loading dose:1 g, Maintenance dose:500 mg q8 h; or Loading dose:1 g LD, Maintenance dose:1 g q12 h (Shaw and Mueller, 2017) Dialysate rate:35 ml/kg/h 1 g q8h 1h infusion (Onichimowski et al, 2020b) Dialysate rate: 0.7-1 L/h 0.25 q24h for MIC ≤2 mg/L >0.5 g q8h for MIC = 16 mg/L (Kawano et al, 2015) Dialysate rate: 30 ml/kg/h 1 g q8h or 2 g q8h or 3 g continuous infusion q24h (Grensemann et al, 2020) Ultrafiltration rate: 22 ± 12 ml/kg/h Dialysate rate: 23 ± 9 ml/kg/h 1 g q12h (MIC ≤1 mg/L) (Seyler et al, 2011) Ultrafiltration rate: 2 L/h Dialysate rate: 1 L/h 500 mg q8h (MIC ≤4mg/L) (Varghese et al, 2015) Ultrafiltration rate: 1.5-2 L/h Dialysate rate: 1-1.5 L/h 1 g q8h Imipenem Ultrafiltration rate: 52 ± 14 ml/kg/h 1.0 g q6h Ultrafiltration rate: 20 or 37 ml/kg/h 0.5 g q6h for MIC ≤2 mg/L, 1.0 g q6h for MIC 4-16 mg/L (Li and Xie, 2019) Dialysate rate: 20 or 37 ml/kg/h 0.5 g q6h for MIC ≤2 mg/L, 1.0 g q6h for MIC 4-16 mg/L (Li and Xie, 2019) Combined flow rate: 20 or 37 ml/kg/h 0.5 g q6h for MIC ≤2 mg/L, 1.0 g q6h for MIC 4-16 mg/L (Li and Xie, 2019) Panipenan CLtot (ml/min) = (1.2 creatinine clearance + 66.5) +0.86 (dialysate rate+ ultrafiltration rate) CLtot <80 ml/min, 0.5 q12h or 1.0 g q15h; 80 ≤ CLtot ≤120 ml/min, 0.5 q8h or1.0 g q12h; 120 ≤ CLtot ≤160 ml/min, 0.5 g q6h or1.0 g q8h (Hayakawa et al, 2006) Biapenan --Ultrafiltration rate: 1,000 ml/h Dialysate rate: 500 ml/h 300 mg q6h (Akashita et al, 2015) (Continued) (Eyler et al, 2014) Combined flow rate: 36-51 ml/h/kg 500 mg q24h, 750 mg q24h, 500 mg q12h, or 1,000 mg q24h (Eyler et al, 2014)…”
Section: Cvvh Cvvhd Cvvhdfmentioning
confidence: 99%
See 1 more Smart Citation
“…Flucloxacillin Ultrafiltration rate: 57 ± 9 ml/min 4.0 g q8h (Meyer et al, 2003) --1 g q8h 1h infusion (Onichimowski et al, 2020b) Dialysate rate: 20-35 ml/kg/h 2 g q12 h; or Loading dose:1 g, Maintenance dose:500 mg q8 h; or Loading dose:1 g LD, Maintenance dose:1 g q12 h (Shaw and Mueller, 2017) Dialysate rate:35 ml/kg/h 1 g q8h 1h infusion (Onichimowski et al, 2020b) Dialysate rate: 0.7-1 L/h 0.25 q24h for MIC ≤2 mg/L >0.5 g q8h for MIC = 16 mg/L (Kawano et al, 2015) Dialysate rate: 30 ml/kg/h 1 g q8h or 2 g q8h or 3 g continuous infusion q24h (Grensemann et al, 2020) Ultrafiltration rate: 22 ± 12 ml/kg/h Dialysate rate: 23 ± 9 ml/kg/h 1 g q12h (MIC ≤1 mg/L) (Seyler et al, 2011) Ultrafiltration rate: 2 L/h Dialysate rate: 1 L/h 500 mg q8h (MIC ≤4mg/L) (Varghese et al, 2015) Ultrafiltration rate: 1.5-2 L/h Dialysate rate: 1-1.5 L/h 1 g q8h Imipenem Ultrafiltration rate: 52 ± 14 ml/kg/h 1.0 g q6h Ultrafiltration rate: 20 or 37 ml/kg/h 0.5 g q6h for MIC ≤2 mg/L, 1.0 g q6h for MIC 4-16 mg/L (Li and Xie, 2019) Dialysate rate: 20 or 37 ml/kg/h 0.5 g q6h for MIC ≤2 mg/L, 1.0 g q6h for MIC 4-16 mg/L (Li and Xie, 2019) Combined flow rate: 20 or 37 ml/kg/h 0.5 g q6h for MIC ≤2 mg/L, 1.0 g q6h for MIC 4-16 mg/L (Li and Xie, 2019) Panipenan CLtot (ml/min) = (1.2 creatinine clearance + 66.5) +0.86 (dialysate rate+ ultrafiltration rate) CLtot <80 ml/min, 0.5 q12h or 1.0 g q15h; 80 ≤ CLtot ≤120 ml/min, 0.5 q8h or1.0 g q12h; 120 ≤ CLtot ≤160 ml/min, 0.5 g q6h or1.0 g q8h (Hayakawa et al, 2006) Biapenan --Ultrafiltration rate: 1,000 ml/h Dialysate rate: 500 ml/h 300 mg q6h (Akashita et al, 2015) (Continued) (Eyler et al, 2014) Combined flow rate: 36-51 ml/h/kg 500 mg q24h, 750 mg q24h, 500 mg q12h, or 1,000 mg q24h (Eyler et al, 2014)…”
Section: Cvvh Cvvhd Cvvhdfmentioning
confidence: 99%
“…Early study showed that the minimum dosages to achieve T > MIC of more than 30% at filtrate-dialysate flow rates of 1.4, 2.8, and 5.6 L/h were 300 mg q12 h, 600 mg q12 h, and 600 mg q12 h, respectively (Ikawa et al, 2008). Biapenem 300 mg q6h might be an appropriate dose under continuous hemodiafiltration (ultrafiltration rate: 1,000 ml/h, dialysate rate: 500 ml/h) (Akashita et al, 2015). Both MICs of pathogens and CRRT effluent flow rates should be considered during biapenem dosing adjustment.…”
Section: Biapenemmentioning
confidence: 99%
“…Clearance never exceeds the liquid inflow rate to dialyzer (Q B in ) or the dialysis outflow rate (Q HDF = Q F + Q D ), and the slower flow is rate-determining in blood purification therapy [ 4 , 15 17 ]. If Q B in < Q D + Q F and assuming complete removal of the drug from the blood, the maximum clearance is defined by Q B in .…”
Section: Discussionmentioning
confidence: 99%
“…Биапенем эффективно удаляется из плазмы во время проведения заместительной почечной терапии (ЗПТ) при сепсисе -продлённой веновенозной гемофильтрации и вено-венозной гемодиафильтрации (ВВГДФ) [43][44][45][46]. Во время проведения ВВГДФ период полувыведения из плазмы крови и фильтрата-диализата составил 3,0 и 3,2 ч, Клиренс ВВГДФ был 1,53 л/ч, а клиренс, не связанный с ВВГДФ -4,9 л/ч.…”
Section: карбапенемunclassified
“…Во время проведения ВВГДФ период полувыведения из плазмы крови и фильтрата-диализата составил 3,0 и 3,2 ч, Клиренс ВВГДФ был 1,53 л/ч, а клиренс, не связанный с ВВГДФ -4,9 л/ч. На основании фармакодинамического моделирования 90% вероятность достижения фармакодинамической цели (40% T > MIC 2 мг/л ) достигалась при назначении биапенема в дозе 300 мг каждые 6 ч при проведении ЗПТ [43]. В другой работе [44] клиренс биапенема, связанный с ВВГВФ, был 1,3 л/м, а клиренс, не связанный с ВВГДФ -6,1 л/ч.…”
Section: карбапенемunclassified